Familial diffuse comedones, different entity or variant of familial dyskeratotic comedones: a case report - Thokchom, Nandakishore; Kongbam, Linda; Bhattacharjee, Nandita; Salam, Erika (International Journal of Research in Dermatology, 2020)
Familial dyskeratotic comedones(FDC) is a rare autosomal dominant genodermatosis characterized by numerous comedones with dyskeratosis in histology. We report a case of 43-year-old woman and her 16-year-old daughter presenting with extensive diffuse comedones on the face, trunk and proximal extremities. Mild slate-grey pigmentation of face in the mother was an additional finding. Skin biopsy showed crateriform invagination with parakeratotic lamellae filled with keratinous material in the epidermis but no dyskeratosis or acantholysis. The case resembles FDC as described earlier. However, certain features like presence of hyperpigmentation and minimal hyperkeratotic papules, and absence of dyskeratosis or acantholysis may suggest that diffuse familial comedones exist as a different genodermatosis.